2010
DOI: 10.1302/0301-620x.92b11.24504
|View full text |Cite
|
Sign up to set email alerts
|

Early failure of the Ultima metal-on-metal total hip replacement in the presence of normal plain radiographs

Abstract: Metal-on-metal total hip replacement has been targeted at younger patients with anticipated long-term survival, but the effect of the production of metal ions is a concern because of their possible toxicity to cells. We have reviewed the results of the use of the Ultima hybrid metal-on-metal total hip replacement, with a cemented polished tapered femoral component with a 28 mm diameter and a cobalt-chrome (CoCr) modular head, articulating with a 28 mm CoCr acetabular bearing surface secured in a titanium alloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 53 publications
3
64
0
Order By: Relevance
“…This was unexpected given that the literature suggests that steep cup inclination is associated with increased release of metal wear debris [7,27,30,31] and increased wear is associated with pseudotumor formation [15,22]. However, there is some recent evidence of high rates of devastating soft tissue reactions in patients with well-positioned MOM hip prostheses [8], which supports our findings. Importantly, our results were unlikely due to the low validity of radiographic measurement of cup position [13,21] because we used three-dimensional CT to measure cup position in all cases.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This was unexpected given that the literature suggests that steep cup inclination is associated with increased release of metal wear debris [7,27,30,31] and increased wear is associated with pseudotumor formation [15,22]. However, there is some recent evidence of high rates of devastating soft tissue reactions in patients with well-positioned MOM hip prostheses [8], which supports our findings. Importantly, our results were unlikely due to the low validity of radiographic measurement of cup position [13,21] because we used three-dimensional CT to measure cup position in all cases.…”
Section: Discussionsupporting
confidence: 82%
“…Some authors suggested that pseudotumors occurred as a result of an adverse reaction to metal wear debris and raised metal ion levels [15,17,35,36], with several small studies finding a direct association with increased component wear rates [22,25] and raised levels of chromium and cobalt ions [15,35]. However, recent evidence suggests pseudotumors are common in patients with asymptomatic MOM THA [23] and in patients with low metal ion levels and a well-positioned cup [8]. The roles of excess wear and patient-specific sensitivity to metal wear debris in the pathogenesis of pseudotumors remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial reports were satisfactory [5,14,22,28,29], subsequent research demonstrated unacceptable early failure rates of monoblock MoM THAs, resulting in a substantial revision burden [2-4, 6, 7, 10, 12, 13, 15, 18, 19, 21, 24, 25, 27, 30, 32, 33, 36]. These revisions can be complicated by extensive soft tissue and bony defects, persistence of adverse local tissue reaction as well as problems associated with the general need to reduce the head size at the time of revision, perhaps increasing the likelihood of dislocation [1,3,7,10,13,18,19,23,25,31,33]. Previous studies reporting on the early complications after these revisions are limited and generally of small number [3,10,31,35].…”
Section: Introductionmentioning
confidence: 99%
“…First, by confining our review to studies that included quantitative or semiquantitative grading of the histologic findings, we excluded many publications that have used only qualitative descriptions of periarticular findings [5,12,29,35,42,44,46] or that have focused on particle quantitation [13,30,45], cytokine detection [9,21], or lymphocyte subsets [29]. Among the studies that have graded morphologic features of periprosthetic tissues, many have not included conventional metal-on-PE or ceramic-on-polyethylene cases as controls, and differences in grading criteria among studies preclude pooling the data into larger groups.…”
Section: Discussionmentioning
confidence: 99%